The influence of pretend play on children's social communication skills - Hajerah, Hajerah; Syamsuardi, Syamsuardi; Alim Amri, Nur; Amri, Nurzil; Maula, Inayatul (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background : Early childhood development, crucial between ages 0-6, encompasses cognitive, social-emotional, and communication skills. Language development theories emphasize communication as a vital aspect of early childhood growth. Children's ability to express themselves supports their learning process and social interactions. Pretend play, involving role-playing and imagination, is a key activity that stimulates language and social skills in children. In urban areas, low social education levels often lead to inappropriate communication styles, making effective early interventions essential.Aim : This study aims to investigate the influence of pretend play on the social communication skills of children in a kindergarten in Makassar City. It seeks to determine whether pretend play can effectively enhance these skills among young children.Method : A quantitative approach with a One Group Pretest-Posttest Design was employed. Data were collected from 20 children through direct observation and pre- and post-intervention evaluations. Validity and reliability tests ensured the research instruments' accuracy.Result : Children who participated in the pretend play program showed significant improvement in social communication skills. The average score increased from 29 (61.90% of the ideal score) before the intervention to 42 (93.65%) after the intervention.Conclusion : Pretend play significantly enhances children's social communication skills, making it a valuable method in early childhood education. Its application can positively impact language development, creativity, and character formation.